Uncovering the Epigenetic Marks Involved in Mediating Salt Stress Tolerance in Plants - Singroha, Garima; Kumar, Satish; Gupta, Om Prakash; Singh, Gyanandra Pratap; Sharma, Pradeep (Frontiers in Genetics, 2022)
The toxic effects of salinity on agricultural productivity necessitate the development of salt stress tolerance in food crops in order to meet the escalating demands. Plants use sophisticated epigenetic systems to fine-tune their responses to environmental cues. Epigenetics is the study of heritable, covalent modifications of DNA and histone proteins that regulate gene expression without altering the underlying nucleotide sequence and consequently modify the phenotype. Epigenetic processes such as covalent changes in DNA, histone modification, histone variants, and certain non-coding RNAs (ncRNA) influence chromatin architecture to regulate its accessibility to the transcriptional machinery. Under salt stress conditions, there is a high frequency of hypermethylation at promoter located CpG sites. Salt stress results in the accumulation of active histones marks like H3K9K14Ac and H3K4me3 and the downfall of repressive histone marks such as H3K9me2 and H3K27me3 on salt-tolerance genes. Similarly, the H2A.Z variant of H2A histone is reported to be downregulated under salt stress conditions. A thorough understanding of the plasticity provided by epigenetic regulation enables a modern approach to genetic modification of salt-resistant cultivars. In this review, we summarize recent developments in understanding the epigenetic mechanisms, particularly those that may play a governing role in the designing of climate-smart crops in response to salt stress